Cranial osteology in Tinamidae (Birds: Tinamiformes), with systematic considerations - Silveira, Luís Fábio; Höfling, Elizabeth (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2007)
The cranial osteology of Nothura maculosa is described and compared with species belonging to other seven genera of tinamous (Tinamidae). Dried, spirit preserved and stained specimens were used for the description and comparison. Young birds showing open sutures proved to be useful in determining the structural contribution of each bone. Results allow recognition of characters common to all genera, such as the presence of an articular surface in the dorsal portion of the otic process of the quadrate, the incomplete fusion of the caudal portion of the vomer and the presence of only one articular surface between the quadrate bone and the skull. We also recognize two groups in the family: one containing the birds belonging to the genera Tinamus and Crypturellus, which have a chain of supraorbital ossicles, a small choanal pit and a well-developed pseudotemporal tubercle, among other characters. A second group, including the birds belonging to the genera Nothura, Rhynchotus, Nothoprocta, Taoniscus, Eudromia and Tinamotis, can be distinguished by a discrete postorbital process, a large choanal pit and a discrete pseudotemporal tubercle. Besides, this group does not possess a chain of supraorbital ossicles as in the first group.